Valuation of Biological Assets at Fair Value - A. O. Beryoza (Мир новой экономики, 2019)
Today the globalisation of the world market leads to the necessity of constructive interaction in the international market and forming common standards of accounting. Transnational corporations as a phenomenon of worldwide integration are businesses with units in different countries of the world. Special issues of information support of management in agricultural organisations have become very important in the conditions of the market economy. Clear and transparent accounting in such enterprises requires the existence of common international standards. Such standards could become International Financial Reporting Standards (IFRS). They are designed to provide an understanding of financial processes in different countries for the interaction between investors and potential investment projects located in different national accounting systems. The standard “Agriculture” has great importance for the Russian Federation. Agriculture is one of the leading sectors of our country, supplying products for both domestic and foreign market. Accordingly, the adoption of this standard and the implementation of its provisions is an important and urgent issue of today’s economic reality. Introduction of this standard leads to the formation of fundamentally new methodological bases of the accounting of agricultural activities based on the market value of assets because paragraphs 12–13 of this Standard states that during the initial and subsequent valuation of biological assets will be measured at their fair value fewer costs to selling. Thus, the need to allocate biological assets in the separate account-economic category, their reflection in the accounting at fair value by the provisions of IAS 41 has determined the relevance of the topic, goal, objectives and logic of the article.